Evaluasi Frame Sepeda saat Tabrakan Dengan Metode Ekplisit Elemen Hingga - Ardi Wiranata; Abdul Arief; Heru Santoso Budi Rochardjo (Department of Mechanical Engineering, Universitas Andalas, 2019)
In this paper, numerical method of crash impact by using explicit dynamic model was used to evaluate the bike frame design. Frontal impact simulation model was carried out to understand the characteristics of energy absorption, stress distribution and deformation of the bike frame. Carbon fiber T300 composite with elasticity modulus 129,79 GPa and overall frame weight is 1,8 kg was used in this simulation as material properties. Hashin damage criteria was used in this numerical analysis since this criteria was widely used to assess composite material damage simulation. In this study Head Tube angle (HTA) and Top Tube Angle (TTA) was modified. The modified HTA was varied from 69O to 76O and TTA was 70O to 86O. This modification was based on the original frame design which the HTA and TTA are 71.5O and 74O respectively. This modification was aimed to find the effect of HTA and TTA modification to energy absorption and stress distribution in the bike frame design. Simulation result shows that TTA and HTA modification affect the energy absorption of the bike frame. The smaller the energy absorption of the bike frame shows that the frame has poor quality of stress distribution.